2016
DOI: 10.1007/s00261-016-0805-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of diffusion-weighted MRI and apparent diffusion coefficient measurements for predicting the response of locally advanced rectal cancer to neoadjuvant chemoradiotherapy

Abstract: DW-MRI may have a significant role in the restaging and in the evaluation of post-CRT response of locally advanced rectal cancer. Quantitative analysis of DWI through ADC map may result in a promising noninvasive tool to evaluate the response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Although our results are concordant with those reported by Kim et al [32], previous studies could determine an optimal cutoff value for postRCT ADCmean to predict good re sponders with a sensitivity of 77.3-88.4 %, specificity of 66.7 % and accuracy of 80.7-87 % [13,17,18,[20][21][22][23]36]. The ∆ADCmean showed a sensitivity of 63.4-72 % and specificity of 66.7-82 % to predict complete response [13,21,36]. Several methodological issues could explain these discrepancies [37].…”
Section: Predictive Value Of Imaging Parameterssupporting
confidence: 92%
“…Although our results are concordant with those reported by Kim et al [32], previous studies could determine an optimal cutoff value for postRCT ADCmean to predict good re sponders with a sensitivity of 77.3-88.4 %, specificity of 66.7 % and accuracy of 80.7-87 % [13,17,18,[20][21][22][23]36]. The ∆ADCmean showed a sensitivity of 63.4-72 % and specificity of 66.7-82 % to predict complete response [13,21,36]. Several methodological issues could explain these discrepancies [37].…”
Section: Predictive Value Of Imaging Parameterssupporting
confidence: 92%
“…Regardless of the definition of response used in these reports (i.e. good or complete response), all studies reported an increase in mean tumour ADC after CRT, 36,39,42,49,[51][52][53][54][55][56][57][58] which is thought to be due to radiation-induced cellular damage and necrosis. 91,92 The disruption of cell membranes reduces the diffusion restriction and therefore increases the ADC.…”
Section: Nodal Restagingmentioning
confidence: 99%
“…Both the final post-CRT ADC and the relative increase in ADC (∆ADC%) were typically higher in the favourable response groups, with statistically significant results in the majority of studies . 36,42,[52][53][54][55][57][58][59][60][61][62][63][64][65][66][67][68][69][70][78][79][80][82][83][84] In addition, several studies found significantly higher pre-CRT ADC values in the unfavourable response groups, 42,[53][54][55][56][63][64][65][66][72][73][74]77,78 although a similar number of studies did not find a significant difference in pre-CRT ADC between response groups. 51,52,58,59,61,62,64,[67][68]…”
Section: Nodal Restagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADC value offers quantitative examination and provides benign and malignant discrimination. Low ADC values reflect dense cellular structures and aggressiveness of the tumor . Additionally, cellular proliferation rate, size of nucleus, intracellular macromolecules, nucleus‐cytoplasm rate, and size of the extracellular matrix may affect the value of ADC .…”
mentioning
confidence: 99%